Effect of Methyl Jasmonate and Mannitol Application on Growth and Eugenol Content in Callus Cultures of Carnation (Plant Tissue Culture and Biotechnology, 2017)
A protocol for callus induction from leaves of carnation is established. MS fortified with 2.0 mg /l 2,4‐D and 0.5 mg/l Kn was found to be the appropriate medium for producing callus cultures. Methyl jasmonate at 20 μM concentration showed the highest growth rate (98.21 mg/day) while mannitol concentrations at 2% gave the peak growth rate (97.1 mg/day).The highest content of eugenol (14.65 μg/100 g calli) was recorded with medium containing 20 μM methyl jasmonate followed by 8.16 μg/100 g calli with 10 μM methyl jasmonate. In presence of 0.5% mannitol, maximum eugenol content (18.00 μg/100 g calli) was obtained.Plant Tissue Cult. & Biotech. 27(2): 227-240, 2017 (December)